Impact of Library User Education Program on Undergraduate Students in Benue State University, Makurdi, Nigeria - Joseph Ahemba, Gbuushi,; Theophilus Terwase, Ubwa, (European Scientific Journal, ESJ, 2018)
The study sought to examine the impact of user education on the utilization of library resources by undergraduate students of Benue State University, Makurdi. The study adopted the survey research design and the population consisted of 25,232 regular undergraduate students in 7 faculties which a sample size of 380 respondents were selected using proportional random sampling technique. Self-developed questionnaires were distributed among sample undergraduate students. However, only three hundred and forty one 341 (89.73%) questionnaires were returned in good shape and analyzed using frequency distribution, percentage and mean. The findings of the study revealed that user education positively impacted the undergraduate students’ use of library resources and the academic performance. The method employed in teaching user education includes lecture method, independent assignment, and practical exercises among others. The study identified some problems that includes; over population, lack of instructional materials, poor monitoring of staff, inadequate qualified staff, limited time allocation, inadequate accommodation and space. The strategies that can be adopted to enhance effective user education to undergraduate students as indicated in the findings includes; provision of adequate staff, proper ventilation and illumination of venue, regular monitoring and control of user education procedures, adjustment of user education time to suit students, positive attitude of staff to the program among others. The study concludes that the library occupies a central place in the achievement of educational objectives of the students and this has made user education indispensable in the library.